2019
DOI: 10.3390/min9050316
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microbial Communities Associated with Ceramic Raw Materials as Potential Contributors for the Improvement of Ceramic Rheological Properties

Abstract: Technical ceramics are being widely employed in the electric power, medical and engineering industries because of their thermal and mechanical properties, as well as their high resistance qualities. The manufacture of technical ceramic components involves complex processes, including milling and stirring of raw materials in aqueous solutions, spray drying and dry pressing. In general, the spray-dried powders exhibit an important degree of variability in their performance when subjected to dry-pressing, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Analysis of the fungal communities demonstrated that Mortierella occupied most of the communities. Motierella is commonly found in cave soils and has been identified in moonmilk in many caves (Rutherford and Huang, 1994;Garcia-Sanchez et al, 2019).…”
Section: Taxonomic Composition Of Microbial Communities In the Two Tymentioning
confidence: 99%
“…Analysis of the fungal communities demonstrated that Mortierella occupied most of the communities. Motierella is commonly found in cave soils and has been identified in moonmilk in many caves (Rutherford and Huang, 1994;Garcia-Sanchez et al, 2019).…”
Section: Taxonomic Composition Of Microbial Communities In the Two Tymentioning
confidence: 99%
“…Micrococcus luteus is a coccus shaped gram-positive bacteria. It is an aerobic exopolysaccharide producing bacteria that may be found on the skin, mouth and sometimes in the throat of mammals 13,14 . Oral microbial flora of reptiles includes bacteria from Proteus, Porphyromonas, Micrococcus, Salmonella and Staphylococcus genera 5,8,15 .…”
Section: Resultsmentioning
confidence: 99%
“…Technical ceramics are classified based on functionality such as biocompatibility, electrical properties, optical properties, mechanical strength, and resistance to high temperatures according to the following types: Medical ceramics; electroceramics; optical ceramics; structural ceramics and ceramics for extreme conditions; ceramics for energy transfer, storage and conversion; and other types of ceramics [96,97].…”
Section: Classification Of Technical Ceramics and Its Workability By Edmmentioning
confidence: 99%